Identification of Cucurbitacin E Accumulated in Leaves and Fruits of the Iraqi Citrullus colocynthis During Two Seasons with Antioxidant Activity - Hind E. Mohammed; Ula M.N. Al-Mousawi; Amjed H. Khamees; Haider AL Wafi (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The experiment was conducted by the Department of Pharmacognosy and Medicinal plants, College of Pharmacy, Basrah university during the agricultural season of 2023-2024, to investigate the content of cucurbitacin E in various portions of Citrullus colosynthis (leaves and fruits). The hot continuous method by reflux apparatus was used to extract the leaves and fruits of plant with different solvents, including chloroform and hexane. Cucurbitacin E is identified by thin-layer chromatography (TLC). The concentration of cucurbitacin was quantified once via high-performance liquid chromatography (HPLC). The antioxidant activity of the chloroform extract and cucurbitacin E was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging method, with vitamin C serving as the standard. In summer, the chloroform extract of leaves exhibits a higher concentration than the other extracts (11. μg ml-1). However, in winter, the chloroform extract of fruits has a greater concentration (20 μg ml-1). The hexane extract is not advisable for two seasons. The findings indicated a non- significant difference between the antioxidant efficacy of chloroform extract and cucurbitacin E, as assessed by the DPPH radical scavenging activity, with IC50 values of 0.75, 1.52, and 1.61 for vitamin C, chloroform extract, and cucurbitacin E, respectively.